Evaluation of a male engagement intervention to transform gender norms and improve family planning and HIV service uptake in Kabale, Uganda. Issue 10 (3rd October 2017) - Ghanotakis, Elena; Hoke, Theresa; Wilcher, Rose; Field, Samuel; Mercer, Sarah; Bobrow, Emily A.; Namubiru, Mary; Katirayi, Leila; Mandera, Immaculate
ABSTRACT: Men's limited understanding of family planning (FP) and harmful cultural gender norms pose obstacles to women's FP use. Thirty-two model men called 'Emanzis' were recruited from the community in Kabale, Uganda to lead men from their peer group through a 10-session curriculum designed to transform gender norms and motivate men to engage in FP and HIV services. Cross-sectional surveys were conducted before ( n  = 1251) and after ( n  = 1122) implementation. The Gender Equitable Men (GEM) Scale was used to assess the effect on gender attitudes. The intervention achieved negligible changes in responses to GEM items. Improvements in some gender-influenced health-seeking behaviours and practices in men were noted, specifically in visiting health facilities, HIV testing, and condom use. For future application, the intervention should be adapted to require higher peer educator qualifications, longer intervention duration, and more frequent supervision. Practical guidance is needed on where to direct investments in gender-transformative approaches for maximum impact.